2019
DOI: 10.1002/marc.201800909
|View full text |Cite
|
Sign up to set email alerts
|

A Three‐Armed Polymer with Tunable Self‐Assembly and Self‐Healing Properties Based on Benzene‐1,3,5‐tricarboxamide and Metal–Ligand Interactions

Abstract: The dynamic nature of supramolecules makes them useful in the fields of smart devices. The combination of multiple dynamic interactions in one material may bring some enhanced properties in mechanical property, self‐healing property, or recyclability. Thus, it is significantly meaningful to design new materials with multi‐dynamic bonds and clarify their bonding mechanisms. Here, a novel three‐armed polymer based on benzene‐1,3,5‐tricarboxamide (BTA) is developed and the polymer could be further complexed by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…As a weak dynamic covalent bond, the disulfide bond can endow the materials with self-healing properties at lower temperature. 2-HEDS is a small molecule with disulfide bonds and active hydroxyl groups at both ends. Therefore, HEDS is widely used in the preparation of self-healing polymers based on disulfide bonds. ,, Wang et al prepared colorless and transparent PUs based on PTMEG, XDI, and HEDS. After being treated at 80 °C for 24 h, the healing efficiency of this PU reached only 37–39%.…”
Section: Shape-memory and Self-healing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a weak dynamic covalent bond, the disulfide bond can endow the materials with self-healing properties at lower temperature. 2-HEDS is a small molecule with disulfide bonds and active hydroxyl groups at both ends. Therefore, HEDS is widely used in the preparation of self-healing polymers based on disulfide bonds. ,, Wang et al prepared colorless and transparent PUs based on PTMEG, XDI, and HEDS. After being treated at 80 °C for 24 h, the healing efficiency of this PU reached only 37–39%.…”
Section: Shape-memory and Self-healing Materialsmentioning
confidence: 99%
“…There are some reversible covalent interactions such as the DA reaction, acylhydrazone bond, disulfide bond, , and alkoxyamine bond, , which can make the polymer exhibit self-healing properties. The reversible noncovalent interactions used in self-healing polymers include crystallization, , hydrogen bonds, , ionic interactions, , metal–ligand interactions, , and hydrophobic interactions …”
Section: Introductionmentioning
confidence: 99%
“…A widely employed and studied molecule in supramolecular chemistry is benzene-1,3,5-tricarboxamide (BTA) [13][14][15][16][17][18][19][20]. Due to its oblate shape and specific chemical structure, BTA forms columnar aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…[16,23,32] Among these supermolecular interactions, metal-ligand interactions offered a feasible strategy to be introduced into the polymeric materials' network, because there is no need especially synthetic modification for the backbone, as well as the metal ions used for ligand, are diverse. [33][34][35][36] What is more, tuning mechanical properties of materials are facilely achieved by changing the metal/ligand ratio. [7] The ideal ligand sulfur within thioether bond, disulfide bond, and thiourethane bond can coordinate with various metal or metal ions, including Ag + , Cu − , Cu 2+ , Au nanoparticles, and Ag nanoparticles et al [30,37,38] Some researchers utilized the silver (Ag) nanoparticles-thioether coordination to prepare thioethersilver polymer composites, which was found that the low adhesion between polymer resin and metal nanoparticles attenuated the mechanical performance of the hybrid materials.…”
Section: Introductionmentioning
confidence: 99%